The perspective of university academics on remote teaching during Covid-19 pandemic - Zhwan Dalshad Abdullah (Malikussaleh Journal of Mathematics Learning (MJML), 2021)
Coronavirus disease 2019 (COVID-19) has impacted global education, and to prevent the spread of disease, the world have adopted remote teaching. The aim of this study was to determine the university academics perspective towards various aspects of remote teaching during COVID-19 pandemic. According to the findings, the majority of academics had no remote teaching prior experiences and most of them appeared to be unsatisfied with the provided online training of online teaching, online teaching platforms, Internet access, students’ participation, online assessment, delivering the content of the subjects they taught, and teaching practical-based subjects. The current study provided essential insights for policymakers in higher education to look over the aspects that hinder the process of remote teaching in Iraq.